2018
DOI: 10.21307/jelpp-2018-002
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of leadership in early childhood education: Tensions and complexities between concepts and practices

Abstract: Effective leadership within early childhood settings is aligned with the perceived successful implementation of high quality care and education programmes (Thornton, Tamati, Clarkin-Philips, Aitken & Wansbrough, 2009). With growing attention on the role early childhood education (ECE) plays in preparing children to be successful in their lives, it is not surprising that there is increased focus on the work and impact of educational leaders in this endeavour. An expanding body of research specifically exploring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 22 publications
0
48
0
1
Order By: Relevance
“…That’s one of the unintended consequences of this model, that the conversations are rich and there are opportunities for learning.Material and financial resources were committed to professional learning on leadership and management. Professional learning incorporated transmission of technical knowledge on regulations, policy and funding (Rodd, 2013), and also innovation in leadership practice (Klevering & McNae, 2018). This learning enabled independent decision-making and flexible approaches to funding and policy to improve children’s access to ECE.…”
Section: Resultsmentioning
confidence: 99%
“…That’s one of the unintended consequences of this model, that the conversations are rich and there are opportunities for learning.Material and financial resources were committed to professional learning on leadership and management. Professional learning incorporated transmission of technical knowledge on regulations, policy and funding (Rodd, 2013), and also innovation in leadership practice (Klevering & McNae, 2018). This learning enabled independent decision-making and flexible approaches to funding and policy to improve children’s access to ECE.…”
Section: Resultsmentioning
confidence: 99%
“…It would be expected that the higher profile and clearer understanding of the concept of leadership would mean that the difference between leadership and management is better understood now than in 2009. Klevering and McNae (2018), reporting on a recent study of New Zealand early childhood leaders' interpretations of leadership and enactment of leadership practice, have, however, warned that that there is still some confusion between the terms. These authors suggest that there is sometimes a focus on management at the expense of educational leadership in the private sector.…”
Section: Leadership Vs Managementmentioning
confidence: 99%
“…In personal communication, Ministry personnel have in the past used the argument that the Ministry is not required to offer the support provided for leadership in schools to early years' services because they are not part of the compulsory sector. It has also been suggested that the Ministry is reluctant to fund programmes that will be accessible for profit as well as non-profit services (Klevering & McNae, 2018). Leadership in the sector has recently been described as "largely devoid of policy direction and resourcing initiatives" (Clarkin-Phillips & Morrison, 2018, p. 1).…”
Section: Ongoing Lack Of Emphasis On Leadership In the Sector By The mentioning
confidence: 99%
See 1 more Smart Citation
“…In older preschool age, leadership manifests in a child having a set of personal qualities allowing them to be an informal leader in a group of peers: to execute leading roles in games, manage children's activities, influence their behavior, etc. [2]. Aspiration for dominance presents one of the determinants of the leadership status in older preschool age, moreover, the prevalence in the desire for a certain modality of dominance is observed: either positive (goodwill, readiness to help and provide support) or negative dominance (demonstration of superiority, aggression, the desire to subjugate other children) [3,4].…”
Section: Introductionmentioning
confidence: 99%